Cholesterol promotes clustering of PI(4,5)P2 driving unconventional secretion of FGF2 - Lolicato, Fabio; Saleppico, Roberto; Griffo, Alessandra; Meyer, Annalena; Scollo, Federica; Pokrandt, Bianca; Müller, Hans-Michael; Ewers, Helge; Hähl, Hendrik; Fleury, Jean-Baptiste; Seemann, Ralf; Hof, Martin; et al. (The journal of cell biology, 2022)
FGF2 is a cell survival factor involved in tumor-induced angiogenesis that is secreted through an unconventional secretory pathway based upon direct protein translocation across the plasma membrane. Here, we demonstrate that both PI(4,5)P2-dependent FGF2 recruitment at the inner plasma membrane leaflet and FGF2 membrane translocation into the extracellular space are positively modulated by cholesterol in living cells. We further revealed cholesterol to enhance FGF2 binding to PI(4,5)P2-containing lipid bilayers. Based on extensive atomistic molecular dynamics (MD) simulations and membrane tension experiments, we proposed cholesterol to modulate FGF2 binding to PI(4,5)P2 by (i) increasing head group visibility of PI(4,5)P2 on the membrane surface, (ii) increasing avidity by cholesterol-induced clustering of PI(4,5)P2 molecules triggering FGF2 oligomerization, and (iii) increasing membrane tension facilitating the formation of lipidic membrane pores. Our findings have general implications for phosphoinositide-dependent protein recruitment to membranes and explain the highly selective targeting of FGF2 toward the plasma membrane, the subcellular site of FGF2 membrane translocation during unconventional secretion of FGF2.